Connections of Grasping and Horizontal Hand Movements with Articulation in Czech Speakers - Tiainen, Mikko; Lukavský, Jiří; Tiippana, Kaisa; Vainio, Martti; Šimko, Juraj; Felisberti, Fatima; Vainio, Lari (Frontiers in Psychology, 2017)
We have recently shown in Finnish speakers that articulation of certain vowels and consonants has a systematic influence on simultaneous grasp actions as well as on forward and backward hand movements. Here we studied whether these effects generalize to another language, namely Czech. We reasoned that if the results generalized to another language environment, it would suggest that the effects arise through other processes than language-dependent semantic associations. Rather, the effects would be likely to arise through language-independent interactions between processes that plan articulatory gestures and hand movements. Participants were presented with visual stimuli specifying articulations to be uttered (e.g., A or I), and they were required to produce a manual response concurrently with the articulation. In Experiment 1 they responded with a precision or a power grip, whereas in Experiment 2 they responded with a forward or a backward hand movement. The grip congruency effect was fully replicated: the consonant [k] and the vowel [ɑ] were associated with power grip responses, while the consonant [t] and the vowel [i] were associated with precision grip responses. The forward/backward congruency effect was replicated with vowels [ɑ], [o], which were associated with backward movement and with [i], which was associated with forward movement, but not with consonants [k] and [t]. These findings suggest that the congruency effects mostly reflect interaction between processes that plan articulatory gestures and hand movements with an exception that the forward/backward congruency effect might only work with vowel articulation.